(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the effectiveness of environmental insurance as one of the measures of environmental risk management, environmental risk, a feature of environmental insurance, are ways to improve the business practices of insurance. In particular, attention was paid environmental insurance in the subsurface.